Time Processing in Dyscalculia - Cappelletti, marinella; Freeman, Elliot D.; Butterworth, Brian L. (Frontiers in Psychology, 2011)
To test whether atypical number development may affect other types of quantity processing, we investigated temporal discrimination in adults with developmental dyscalculia (DD). This also allowed us to test whether (1) number and time may be sub-served by a common quantity system or decision mechanisms –in which case they may both be impaired, or (2) whether number and time are distinct –and therefore they may dissociate. Participants judged which of two successively presented horizontal lines was longer in duration, the first line being preceded by either a small or a large number prime (‘1’ or ‘9’) or by a neutral symbol (‘#’), or in third task decide which of two Arabic numbers (either ‘1’, ‘5’, ’9’) lasted longer. Results showed that (i) DD’s temporal discriminability was normal as long as numbers were not part of the experimental design even as task-irrelevant stimuli; however (ii) task-irrelevant numbers dramatically disrupted DD’s temporal discriminability, the more their salience increased, though the actual magnitude of the numbers had no effect; and in contrast (iii) controls’ time perception was robust to the presence of numbers but modulated by numerical quantity such that small number primes or numerical stimuli made durations appear shorter than veridical and the opposite for larger numerical prime or numerical stimuli. This study is the first to investigate continuous quantity as time in a population with a congenital number impairment and to show that atypical development of numerical competence leaves continuous quantity processing spared. Our data support the idea of a partially shared quantity system across numerical and temporal dimensions, which allows dissociations and interactions among dimensions; furthermore, they suggest that impaired number in DD is unlikely to originate from systems initially dedicated to continuous quantity processing like time.